Longshore Bar Deposits in a Modern Fluvial-Dominated Delta: A Case Study from the Wulan Delta, Demak, Central Java, Indonesia - Hasan Tri Atmojo; Achmad Rizal; Farchan Nauval; Djati Wicaksono Sadewo; Adrian Hanenda; Hadi Nugroho; Anis Kurniasih; Irfan Cibaj (Ikatan Ahli Geologi Indonesia, 2016)
The Wulan Delta is located about 30km NE of Semarang city, at the northern coast of Central Java. The delta began to develop in Quaternary with sediment being supplied by the Wulan River. In the last ten years, a longshore bar deposit has been developing at the northern to northeastern part of the delta, reflecting a change in depositional style from a river-dominated delta to a more wave/ longshore current-dominated system.Field work was done recently to determine the stratigraphic pattern, lateral distribution, sand geometry, and the origin of these longshore bar deposits. This included core sampling, sedimentological description and lithology correlation. Forty core samples were taken and 34 out of the 40 cores were used in correlation and interpretation. Qualitative analyses (granulometry) were then conducted on the cored sand deposits to get the sorting, skewness and kurtosis values.The longshore bar deposit of the Wulan Delta was formed by longshore currents that reworked sediment material to the shoreline and deposited sands laterally around the river mouth. Sediment transport dynamics influenced saltation swash and backwash, which are interpreted from the presence of swash cross-stratification as a characteristic of deposition in the foreshore area. The longshore bar deposit was deposited progressively seaward due to rapid sediment influx from up-river and limited accommodation space. The geometry of the sand deposits was measured for three segments of longshore sand bars. At STA LSB 1 it is 2773m long, 830m wide and 0.75m thick. At STA LSB 2 it is 1082m long, 272m wide and 0.5 m thick; and at the last station it is 1276m long, 374m wide and 1m thick.